A systematic review of the social and economic burden of influenza in low- and middle-income countries. Issue 48 (27th November 2015) - de Francisco (Shapovalova), Natasha; Donadel, Morgane; Jit, Mark; Hutubessy, Raymond
Abstract: Objectives: The economic burden of seasonal influenza outbreaks as well as influenza pandemics in lower- and middle-income countries (LMIC) has yet to be specifically systematically reviewed. The aim of this systematic review is to assess the evidence of influenza economic burden assessment methods in LMIC and to quantify the economic consequences of influenza disease in these countries, including broader opportunity costs in terms of impaired social progress and economic development. Methods: We conducted an all language literature search across 5 key databases using an extensive list of key words for the time period 1950–2013. We included studies which explored direct costs (medical and non-medical), indirect costs (productivity losses), and broader economic impact in LMIC associated with different influenza outcomes such as confirmed seasonal influenza infection, influenza-like illnesses, and pandemic influenza. Results: We included 62 full-text studies in English, Spanish, Russian, Chinese languages, mostly from the countries of Latin American and the Caribbean and East Asia and Pacific with pertinent cost data found in 39 papers. Estimates for direct and indirect costs were the highest in Latin American and the Caribbean. Compared to high-income economies, direct costs in LMIC were lower and productivity losses higher. Evidence on broader impact of influenza included impact on the wider national economy, security dimension, medical insurance policy, legal frameworks, distributional impact, and investment flows. Conclusion: The economic burden of influenza in LMIC encompasses multiple dimensions such as direct costs to the health service and households, indirect costs due to productivity losses as well as broader detriments to the wider economy. Evidence from sub-Saharan Africa and in pregnant women remains very limited. Heterogeneity of methods used to estimate cost components makes data synthesis challenging. There is a strong need for standardizing research, data collection and evaluation methods for both direct and indirect cost components.